Superior mesenteric vein aneurysm. A rare clinical entity, a new surgical approach. - Rodrigues Teixeira, José Nuno (2016)
Superior mesenteric vein aneurysms are an extremely rare clinical entity, with a variable clinical presentation and an unpredictable clinical course. The authors present the case of a 41 year old female with a saccular superior mesenteric vein aneurysm incidentally identified on abdominal CT scan. The patient was treated with surgical aneurismectomy with a vascular stapler, and the postoperative recovery was uneventful. She is clinically well two years after surgery.